European „Ghost Airports": EU Law Failure or Policy Failure? The Need for Economic Analysis in State Aid Law (Polish Yearbook of International Law, 2017)
Wasteful spending of public funds, leading to the creation of “ghost airports”, is often described as a regulatory failure and a major defciency in European State aid control. It is pointed out that decisions to build or upgrade an airport are often ill-conceived, poorly implemented, and without economic justifcation. This raises the question whether European law, namely its State aid control system, contains inherent ﬂaws or whether the European Commission’s decision-making process can be improved by increasing reliance on objective economic reasoning under the existing legal framework. Tis article provides an analysis of the decision-making problems leading to failed aid eﬀorts; of the role of the economic approach in State aids; and of the standard of economic assessment required in State aid cases. The article concludes with de lege ferenda postulates.